Biopolymer surface modification of PLGA fibers enhances interfacial shear strength and supports immobilization of rhGDF-5 in fiber-reinforced brushite cement. (March 2021) - Firkowska-Boden, Izabela; Adjiski, Ranko; Bautista, Andres Cordero; Borowski, Andreas; Matziolis, Georg; Jandt, Klaus D.; Kinne, Raimund W.; Bossert, Jörg
Abstract: Incorporation of biodegradable poly(lactic-co-glycolic acid; PLGA) fibers into calcium phosphate cements (CPCs) has proven beneficial for their mechanical properties and the targeted delivery of bone morphogenetic proteins (BMPs). However, the deficiency of functional groups on the PLGA surface results in poor fiber-matrix interfacial strength (ISS), limiting the mechanical improvement, and insufficient surface charge to immobilize therapeutic amounts of BMPs. The present study therefore focused on the: i) functionalization of PLGA fibers using polyelectrolyte multilayers (PEMs) of biopolymers; ii) analysis of their impact on the mechanical properties of the CPC in multifilament fiber pull-out tests; and iii) testing of their applicability as carriers for BMPs using chemical-free adsorption of biotinylated recombinant human growth factor (rhGDF-5) and colorimetric assays. The PEMs were created from chitosan (Chi), hyaluronic acid (HA), and gelatin (Gel) via layer-by-layer (LbL) deposition. Four PEM nanocoatings consisting of alternating Chi/Gel and Chi/HA bilayers with a terminating layer of Chi, Gel or HA were tested. Nanocoating of the PLGA fibers with PEMs significantly enhanced the ISS with the CPC matrix to max. 3.55 ± 1.05 MPa (2.2-fold). The increase in ISS, ascribed to enhanced electrostatic interactions between PLGA and calcium phosphate, was reflected in significant improvement of the composites' flexural strength compared to CPC containing untreated fibers. However, only minor effects on the composites' work of fracture were observed. The adsorption of rhGDF-5 on the PLGA surface was supported by PEMs terminating with either positive or negative charges, without significant differences among the nanocoatings. This proof-of-principle rhGDF-5 immobilization study, together with the augmented ISS of the composites, demonstrates that surface modification of PLGA fibers with biopolymers is a promising approach for targeted delivery of BMPs and improved mechanical properties of the fiber-reinforced CPC. Graphical abstract: Image 1 Highlights: Chitosan (Chi), hyaluronic acid (HA), and gelatin (Gel) created homogenous coating on PLGA fibers via layer-by-layer process. Polyelectrolyte multilayers (PEMs) significantly enhanced the interfacial shear strength (ISS) with the calcium phosphate matrix. Increased ISS led to significant improvement of the composites' flexural strength. PEMs supported the immobilization of bone morphogenetic protein, rhGDF-5.